2018
DOI: 10.1186/s13099-018-0268-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Salmonella enterica serovars recovered from meat products legally and illegally imported into the EU reveals the presence of multiresistant and AmpC-producing isolates

Abstract: BackgroundFood products of animal origin brought into the EU from third countries, both legally and illegally, can harbor foodborne pathogens such as Salmonella enterica. In this study, we examined five S. enterica isolates recovered either from legally imported chicken meat (n = 3) or from meat products confiscated from air travel passengers arriving in Germany (n = 2). The isolates were serotyped and further characterized by antimicrobial susceptibility testing, PCR-detection and sequencing of genes associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…For instance; meat sources; beef, chevon, and mutton contained different serovars of S. enterica isolates which were clonally distinct (Figure 1). This finding corroborated with other studies reported worldwide specifically in Europe (Müller, Jansen, Grabowski, & Kehrenberg, 2018), Africa (Thomas et al, 2020), and Asia (Yang et al, 2019) which isolated different serovars S. enterica in food samples. However, all the guinea fowl and chicken samples contained the same serovar; S. enterica subsp.…”
Section: Con Clus Ionsupporting
confidence: 92%
“…For instance; meat sources; beef, chevon, and mutton contained different serovars of S. enterica isolates which were clonally distinct (Figure 1). This finding corroborated with other studies reported worldwide specifically in Europe (Müller, Jansen, Grabowski, & Kehrenberg, 2018), Africa (Thomas et al, 2020), and Asia (Yang et al, 2019) which isolated different serovars S. enterica in food samples. However, all the guinea fowl and chicken samples contained the same serovar; S. enterica subsp.…”
Section: Con Clus Ionsupporting
confidence: 92%
“…The detection of additional resistance determinants was performed using a set of PCR assays as described previously [ 39 ]. This included determinants mediating resistance to tetracyclines ( tet (A), tet (B), tet (C), tet (D), tet (E), tet (G), and tet (H)), sulfonamides ( sul1 , sul2 and sul3 ), trimethoprim ( dfrA5/dfrA14 , dfrA7/dfrA17 , dfrA1 , and dfrB1/dfrB2 ) phenicols ( cmlA , floR ) and those associated with resistance to quinolones ( qnrA , qnrB , qnrC , qnrD , qnrS , qepA , aac(6′)-Ib-cr , gyrA , gyrB , parC, parE ).…”
Section: Methodsmentioning
confidence: 99%
“…Importation of poultry meat has been suggested as a possible means of the introduction of Salmonella serovars infrequently reported in Europe (Mueller et al, 2018). S. Heidelberg and S. Minnesota, both with multidrug-resistant profiles, including to ESCs and/or FQs, were identified in meat imported from outside the EU into Portugal.…”
Section: Increased Virulence or Resistance To Relevant Therapies For mentioning
confidence: 99%
“…Importation of poultry meat has been suggested as a possible means of the introduction of Salmonella serovars infrequently reported in Europe (Mueller et al., ). S .…”
Section: Assessmentmentioning
confidence: 99%